A case study of group processes and student evaluation of teaching. (2nd January 2017) - Mortenson, Kristian G.; Sathe, Richard S.
ABSTRACT: This paper documents a case study undertaken to understand the effect of group processes on student evaluation of teaching (SET). The study used interviews to investigate the experiences of students in a cohort model Master of Science in Accountancy degree program and how those experiences influenced SET. The cohort served as an extreme example in which group processes played out intensely, allowing the researchers better to examine them. The results showed that the participants' common experience led to frequent discussion about various aspects of the classes and the program. A common topic of discussion was instructor performance. This discussion about instructors, in turn, appeared to affect SET. It also appeared that a mismatching of expectations and realized student–instructor relationships also affected SET.